2022
DOI: 10.3390/ma15155467
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scale Effect on Strength and Deformation Characteristics of Rockfill Materials

Abstract: The hybrid method was adopted to model the original gradation of rockfill materials. According to the specification requirements, three simulated gradations of rockfill materials have been obtained. By the same token, the corresponding maximum particle sizes are 20 mm, 40 mm and 60 mm, respectively. With samples prepared under the same criterion of relative density, the scale effect on strength and deformation characteristics of the rockfill materials were studied by large-scale and consolidated-drained triaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Screening of the filling material on-site (Figure 2a) revealed that particles exceeding 40 mm comprised about 2~5% of the mass, with a non-uniformity coefficient Cu = 9.6~37.1 and a curvature coefficient Cc = 1.8~3.8. For particles that exceed the allowable range of the maximum particle size of the instrument, four methods are often adopted in the laboratory for treatment: the elimination method [25], the similar grading method [26], the equivalent weight replacement method [7] and the mixed method [27]. Since the particle size exceeding 40 mm was less than 10%, the elimination method was used to treat the excess particle size, the maximum particle size of the sample was controlled below 40 mm to meet the requirements of the instrument for the sample size.…”
Section: Experimental Instrument and Materialsmentioning
confidence: 99%
“…Screening of the filling material on-site (Figure 2a) revealed that particles exceeding 40 mm comprised about 2~5% of the mass, with a non-uniformity coefficient Cu = 9.6~37.1 and a curvature coefficient Cc = 1.8~3.8. For particles that exceed the allowable range of the maximum particle size of the instrument, four methods are often adopted in the laboratory for treatment: the elimination method [25], the similar grading method [26], the equivalent weight replacement method [7] and the mixed method [27]. Since the particle size exceeding 40 mm was less than 10%, the elimination method was used to treat the excess particle size, the maximum particle size of the sample was controlled below 40 mm to meet the requirements of the instrument for the sample size.…”
Section: Experimental Instrument and Materialsmentioning
confidence: 99%